Аналіз показників енергоефективності коректора коефіцієнта потужності при різних способах широтно-імпульсної модуляції - Степенко, С.А. (Технічна електродинаміка, 2014)
В роботі проведено аналіз показників енергоефективності для коректора коефіцієнта потужності на основі імпульсного перетворювача при використанні різних типів широтно-імпульсної модуляції. Показано, що в діапазоні частот модуляції 20-180 кГц за умови використання сучасної елементної бази можлива побудова коректорів коефіцієнта потужності з високими показниками енергоефективності (коефіцієнт корисної дії 97%, коефіцієнт гармонік струму 7-13%, коефіцієнт потужності 0,992-0,997). В работе проанализированы показатели энергоэффективности для активного корректора коэффициента мощности на основе повышающего импульсного преобразователя при использовании различных типов широтно-импульсной модуляции. Показано, что в диапазоне частот модуляции 20-180 кГц при использовании современной элементной базы возможно построение активных корректоров коэффициента мощности на основе повышающего импульсного преобразователя, с высокими показателями энергоэффективности (КПД − 97%, коэффициент гармоник тока − 7-13%, коэффициент мощности − 0,992-0,997). The paper is devoted to energy efficiency analysis of power factor corrector based on boost converter by modeling in Matlab Simulink. The different types of pulse-width modulation, including trailing-edge modulation, leading-edge modulation and doubleedge modulation, were investigated. The study shows, that using modern semiconductor devices with modulation in the frequency range 20-180 kHz, it is possible to build an active power factor corrector with high performance (efficiency up to 97%, total harmonic distortion of the input current 7-13%, power factor 0,992-0,997). At frequencies less than 100 kHz the use of leading-edge PWM or double-edge PWM instead of trailing-edge PWM is more efficient based on power factor and total harmonic distortion of the current